EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KREATIF DAN HASIL BELAJAR KOGNITIF SISWA - Suaedin Suaedin; Hunaepi Hunaepi; Saidil Mursali (Bioscientist : Jurnal Ilmiah Biologi, 2014)
National education is expected to produce intelligent Indonesian man, solve life problems and form human beings who are able to think creatively. The result of early observation in SMA Al-Ma'arif NU Al-Manshuriyah Bonder, found the problem among the students are less active in thinking cretif, ask, and learning outcomes are still relatively low. This quasi experimental research was conducted with the aim to know the Effectiveness of Problem Based Learning Model on Improving Creative Thinking Ability and Cognitive Learning Outcomes of Grade X High School Al-Ma'arif NU Al Manshuriyah Bonder. The design used was the Non-Equivalent Control Group Design in two classes taken at random, the XB class as an experimental class taught by Problem Based Learning Model and class XA as control class which was taught by lecture and question and answer method. Data of creative thinking ability and cognitive learning result data were collected by test technique and analyzed by t-test at 5% significance level. The results showed that, the ability of creative thinking in the experimental class and control class has a value of tcount = 5.26 ˃ ttabel = 2.11. While student learning result indicate that thitung (7,75) > ttable (1,671). Based on the results of research can be concluded that Problem-Based Learning Model affects the improvement of creative thinking skills and student cognitive learning outcomes.